May Measurement Month 2019: adherence to treatment and hypertension control in Russia - O. P. Rotar; K. M. Tolkunova; V. N. Solntsev; A. M. Erina; M. A. Boyarinova; A. S. Alieva; E. V. Moguchaya; E. P. Kolesova; E. I. Pavlyuk; O. M. Posnenkova; O. V. Abrosimova; O. M. Drapkina; et al. (Российский кардиологический журнал)
The International Society of Hypertension and the World Hypertension League initiated a blood pressure screening study called May Measurement Month 2019 (MMM19) to improve the detection of elevated blood pressure (BP) and to assess BP control in patients with hypertension (HTN).Aim. To assess adherence to treatment of the hypertensive population according to MMM19 campaign in Russia.Material and methods. During May 2019, 5394 people from 21 regions of Russia took part in the screening. Participation was voluntary and did not imply gender restrictions; all subjects were over 18 years of age. During the screening, BP was measured three times using electronic and mechanical sphygmomanometers, as well as a questionnaire on the diabetes, history of cardiovascular events, smoking, and alcohol consumption was filled. Information was also collected on the date of last BP check and the administration of statins, acetylsalicylic acid and antihypertensive drugs. Data on height and body weight was obtained from respondents.Results. The analysis included data from 5274 participants aged 18 to 96 years (men — 1834 (34,8%)). Median age was 25 years, quartiles — 20 and 49 years. According to MMM19 data, the proportion of HTN patients in the Russian population was 31,9%, and with the exception of participants under 25 years old — 51,5%. Patients with HTN over 25 years old take antihypertensive therapy in 73,6%; 38,6% are characterized by irregular drug intake. Only 11,8% of men and 17,2% of women reach the target blood pressure <130/80 mm Hg. Only 20-30% of patients who used 4-5 antihypertensives reached the target BP level.Conclusion. According to MMM19 in Russia, only a third of high-risk patients measured BP over the past 12 months. There is also low adherence to antihypertensive therapy and inadequate control of HTN. Patients with HTN and a history of cardiovascular events are more likely to take antihypertensives regularly.